Open framework for distributed context management in ubiquitous environments. (25th May 2012) - Lu, Jun–Hong; Wang, Chiung–Ying; Hwang, Ren–Hung
Most previous research into ubiquitous computing has focused on small and ad hoc environments with proprietary infrastructures and protocols. Consequently, context–aware services are usually developed without considering interoperability among different systems, devices and services. This work presents an open framework for ubiquitous environments, with a distributed context management architecture and a communication model based on standard protocols. With this framework, a smart device can search for context–aware services and a service can be easily deployed via standard protocols and distributed context managers. A prototype of the framework has been implemented to demonstrate its feasibility.